The Role of Mothers in Educating Islamic Values for Children in Campurejo Village, Kediri City - Titin Widya Risni; Pamadya Vitasmoro (Journal of Islamic Education Research, 2024)
Speed must be balanced with Islamic values. This balance is needed by the mother's role in educating her children about Islam. This study aims to examine the relationship of faith, worship, and noble character with Islamic values. This study uses the chi-square test of each variable used. Testing relationships without using group data. This finding is that there is no relationship to the mother's role in faith and worship. However, there is a relationship with the noble character practiced by their early childhood in the Campurejo sub-district. Civil Engineering, Faculty of Engineering, Kadiri University